Detection of Staphylococcus aureus virulence gene pvl based on CRISPR strip - Jin, Li; Hu, XiaoFeng; Tian, Yuan; Fang, MengYa; Dong, Xue; Jiang, YaXuan; Han, Yao; Li, Hao; Sun, Yansong (Frontiers in Immunology, 2024)
Staphylococcus aureus (S. aureus) is a prominent pathogen responsible for both hospital-acquired and community-acquired infections. Among its arsenal of virulence factors, Panton-Valentine Leucocidin (PVL) is closely associated with severe diseases such as profound skin infections and necrotizing pneumonia. Patients infected with pvl-positive S. aureus often exhibit more severe symptoms and carry a substantially higher mortality risk. Therefore, it is crucial to promptly and accurately detect pvl-positive S. aureus before initiating protective measures and providing effective antibacterial treatment. In this study, we propose a precise identification and highly sensitive detection method for pvl-positive S. aureus based on recombinase-assisted amplification and the CRISPR-ERASE strip which we previously developed. The results revealed that this method achieved a detection limit of 1 copy/μL for pvl-positive plasmids within 1 hour. The method successfully identified all 25 pvl-positive and 51 pvl-negative strains among the tested 76 isolated S. aureus samples, demonstrating its concordance with qPCR. These results show that the CRISPR-ERASE detection method for pvl-positive S. aureus has the advantages of high sensitivity and specificity, this method combines the characteristics of recombinase-assisted amplification at room temperature and the advantages of ERASE test strip visualization, which can greatly reduce the dependence on professional laboratories. It is more suitable for on-site detection than PCR and qPCR, thereby providing important value for rapid on-site detection of pvl.